PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS, CITRA MEREK, DAN LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN SIMCARD DATA IM3 (STUDI PADA SMA N 1 SUKOREJO) - Anton Purnomo, 12.05.51.0108; Maskur, Ali (Students Journal of Economic and Management, 2016)
With so many communications company in Indonesia, then consumers will be more selective in determining im card that will be used as their needs. The problem in this research is